Correlates of Health Literacy and Its Impact on Illness Beliefs for Emergency Department Patients With Acute Heart Failure. Issue 1 (March 2017) - Kumar, Vijaya Arun; Albert, Nancy M.; Medado, Patrick; Mango, Lynn Marie; Nutter, Benjamin; Yang, Dongsheng; Levy, Phillip
Abstract : Objectives: To study the relationship between health literacy (HL) and socioeconomic, demographic factors and disease-specific illness beliefs among patients who present to the emergency department with heart failure (HF). Background: Maintenance of well-being for patients with HF is partially dependent on appropriate self-care behaviors, which, in turn, are influenced by underlying illness beliefs. HL is a potential modifier of the interaction between behaviors and beliefs. There have been limited investigations studying this relationship among individuals with acute HF. Methods: A cross-sectional study of patients with hemodynamically stable acute HF was conducted. Demographic, education, and social support data were obtained from all patients along with self-reported responses to the 36-item STOFHLA survey, a 14 item HF-specific illness belief questionnaire, and a 5-item self-care adherence survey. General association was assessed using the χ 2 or Fisher exact test, and comparisons were made using the Kruskal–Wallis test. Results: A total of 100 patients (51 females and 49 males) were included, 94% of whom were African-American (mean age [SD]: 57.5 [13.2] years). Inadequate, marginal, and adequate health literacy were present in 35%, 17%, and 48%, respectively, with increasing adequacy among the higher educated ( P < 0.001). Overall, HF illness beliefs were considered to be "inaccurate" (mean score [SD] on a 4-point Likert scale: 2.8 [0.3]) but did correlate positively with improved HL ( r = 0.26; P = 0.008). Conclusion: In this cohort of relatively young, predominantly African-American patients with acute HF, HL was positively correlated with level of education and negatively associated with age and was an important determinant of disease-specific illness beliefs.